Site‐Specific Alkene Hydromethylation via Protonolysis of Titanacyclobutanes. (19th May 2021) - Law, James A.; Bartfield, Noah M.; Frederich, James H.
Abstract: Methyl groups are ubiquitous in biologically active molecules. Thus, new tactics to introduce this alkyl fragment into polyfunctional structures are of significant interest. With this goal in mind, a direct method for the Markovnikov hydromethylation of alkenes is reported. This method exploits the degenerate metathesis reaction between the titanium methylidene unveiled from Cp2 Ti(μ‐Cl)(μ‐CH2 )AlMe2 (Tebbe's reagent) and unactivated alkenes. Protonolysis of the resulting titanacyclobutanes in situ effects hydromethylation in a chemo‐, regio‐, and site‐selective manner. The broad utility of this method is demonstrated across a series of mono‐ and di‐substituted alkenes containing pendant alcohols, ethers, amides, carbamates, and basic amines. Abstract : A method for the direct Markovnikov hydromethylation of unactivated alkenes by protonolysis of titanacyclobutanes has been developed. This approach enables site‐specific incorporation of a methyl group into complex, polyfunctional molecules and has been demonstrated with a series of mono‐ and disubstituted alkenes containing pendant alcohols, ethers, amides, carbamates, and basic amines.